Big Five Personality and Job Burnout among Malaysian Secondary School Teachers - Shi Xian, Lam; Mahfar, Mastura; Mohd Azam Wan Mohd Yunus , Wan; Amat Senin, Aslan (International Journal of Psychosocial Rehabilitation, 2020)
This study was carried out to identify the relationship between personality traits (openness to experience, conscientiousness, extraversion, agreeableness, and neuroticism) and job burnout among Malaysian teachers. A total number of 191 secondary school teachers in the district of Johor Bahru, Malaysia, was selected by using the stratified random sampling method. A NEO-Five Factor Inventory (NEO-FFI) was used as the measurement of Big Five personality, and the Maslach Burnout Inventory-Educator Survey (MBI-ES) was used to measure job burnout of teachers. The Pearson correlation results showed that all the personality traits were significantly related to each dimension of job burnout. The Pearson correlation results indicated that all the dimensions of Big Five personality, except for neuroticism, have negative relationships with emotional exhaustion and depersonalization as well as have positive relationships with personal accomplishment. Neuroticism has a positive relationship with job burnout. The findings put emphasis on the importance of personality traits as possible factors that can be associated with job burnout.